Application of MFCA and ECRS in waste reduction: A case study of electronic parts factory - Kasemset C. (2017)
© IEOM Society International. The objective of this study is to apply Material Flow Cost Accounting (MFCA) and ECRS techniques to reduce material waste in the production of one electronic parts factory in Thailand. The seven steps of MFCA implementation were adopted to locate the source of negative product cost. From MFCA analysis, the negative product cost of material cost (MC) was the biggest amount comparing with other costs. Pareto chart was used to identify the major cause of the problem. Consequently, it was found that at the first process of trigger coil (target product) production line as frame cutting and injection had the highest negative cost of MC. Then, it was found that material waste in form of frame scrap generated at this process was from the inappropriate working method. Thus, the solution was proposed to design a new jig for the cutting operation. The results from MFCA analysis for the improvement showed that the total input cost was decreased from 22,444.46 to 22,300.92 THB and the negative product cost of MC was decreased from 2,557.10 to 2,437.21 THB. In addition, this solution can help in material reduction as 465.50 g. and gained more product as 2,000 pieces per production lot. Moreover, the total benefit for this product was approximately as 23,611.24 THB per month. © IEOM Society International.